Transcriptional role of androgen receptor in the expression of long non-coding RNA Sox2OT in neurogenesis. - Valentina Tosetti; Jenny Sassone; Anna L M Ferri; Michela Taiana; Gloria Bedini; Sara Nava; Greta Brenna; Chiara Di Resta; Davide Pareyson; Anna Maria Di Giulio; Stephana Carelli; Eugenio A Parati; et al. (PLoS ONE)
The complex architecture of adult brain derives from tightly regulated migration and differentiation of precursor cells generated during embryonic neurogenesis. Changes at transcriptional level of genes that regulate migration and differentiation may lead to neurodevelopmental disorders. Androgen receptor (AR) is a transcription factor that is already expressed during early embryonic days. However, AR role in the regulation of gene expression at early embryonic stage is yet to be determinate. Long non-coding RNA (lncRNA) Sox2 overlapping transcript (Sox2OT) plays a crucial role in gene expression control during development but its transcriptional regulation is still to be clearly defined. Here, using Bicalutamide in order to pharmacologically inactivated AR, we investigated whether AR participates in the regulation of the transcription of the lncRNASox2OTat early embryonic stage. We identified a new DNA binding region upstream of Sox2 locus containing three androgen response elements (ARE), and found that AR binds such a sequence in embryonic neural stem cells and in mouse embryonic brain. Our data suggest that through this binding, AR can promote the RNA polymerase II dependent transcription of Sox2OT. Our findings also suggest that AR participates in embryonic neurogenesis through transcriptional control of the long non-coding RNA Sox2OT.